Extracts of Rhizoma polygonati odorati prevent high-fat diet-induced metabolic disorders in C57BL/6 mice. - Ming Gu (Public Library of Science (PLoS), 2013)
Polygonatum odoratum (Mill.) Druce belongs to the genus Polygonatum family of plants. In traditional Chinese medicine, the root of Polygonatum odoratum, Rhizoma Polygonati Odorati, is used both for food and medicine to prevent and treat metabolic disorders such as hyperlipidemia, hyperglycemia, obesity and cardiovascular disease. However, there is no solid experimental evidence to support these applications, and the underlying mechanism is also needed to be elucidated. Here, we examined the effect of the extract of Rhizoma Polygonati Odorati (ER) on metabolic disorders in diet-induced C57BL/6 obese mice. In the preventive experiment, the ER blocked body weight gain, and lowered serum total cholesterol (TC), triglyceride (TG) and fasting blood glucose, improved glucose tolerance test (GTT) and insulin tolerance test (ITT), reduced the levels of serum insulin and leptin, and increased serum adiponectin levels in mice fed with a high-fat diet significantly. In the therapeutic study, we induced obesity in the mice and treated the obese mice with ER for two weeks. We found that ER treatments reduced serum TG and fasting blood glucose, and improved glucose tolerance in the mice. Gene expression analysis showed that ER increased the mRNA levels of peroxisome proliferator-activated receptors (PPAR) γ and α and their downstream target genes in mice livers, adipose tissues and HepG2 cells. Our data suggest that ER ameliorates metabolic disorders and enhances the mRNA expression of PPARs in obese C57BL/6 mice induced by high-fat diet.